Better property rigth, as a resolution mechanism to duplicity of item in the real estate registry - Torres Abarca, Juan Rómulo (2021)
The duplication of registration items in the Real Property Registry is a pathology that the registration system has been facing, and as a consequence brings a conflict of rights between so many holders, as so many ítems coexist. That is why the author considers that the solution should not be limited to just preferring the person who registered their right in the oldest item, but should be verified, by virtue of a study of titles, the origin of the items such as that has been taking place over time, in order to judicially determine, through a process of better property rights, which one is effective.